Evaluation of The Implementation of The Internal Quality Assurance System Using The Cipp Evaluation Model - Suryadi Suryadi; Fajar Erlangga (Universitas Muhammadiyah Mataram, 2021)
The purpose of this study was to determine: the effectiveness of the SPMI implementation at STKIP SITUS Banten using the CIPP evaluation model. The study was conducted at the STKIP Situs Banten using the CIPP evaluation method. To conduct a comprehensive assessment, the CIPP model requires that multiple aspects of a program be considered, including input from representative stakeholders. These aspects are evaluated through four major evaluations context (X1), input (X2), process (X3), and product (X4), which provide data to assess the overall program. Collecting data with a questionnaire filled out by 200 respondents lecturers and education staff. And the research sample was randomly selected. The results showed: Evaluation of the implementation of the internal quality assurance system at STKIP Situs Banten using the CIPP evaluation model was effective category.